Risk perception by UK firms towards the Russian market - Zarkada, Anna K.; Fraser, Campbell (My University, 2002)
One of the factors that affect the foreign market entry decisions of a construction firm is the risk involved. This paper reviews the concept of risk and its manifestations in the volatile socio-economic and political climate of Russia, a market previously inaccessible to the international construction industry and now full of opportunities and threats. It also presents the perceptions of political risk and Russia's market potential held by the marketing managers of UK construction firms that are involved in the Russian market. Conforming to international marketing theory, their decisions are influenced by a number of factors, with political risk being one of them. The paper additionally establishes that practicing marketers' perceptions vary according to the time and form of involvement in the market.
Keywords: International marketing; Political risk analysis; Russia; UK